(untitled) (International Journal of Food and Nutritional Sciences, 2019)
The Banking and Investment sector has been providing quite low returns on investment in the past few years. Demonetization, Coronavirus induced Pandemic, Slower pace of Economic Growth are few of the reasons that can be attributed to it. All of the above has diverted investors focus towards Cryptocurrency. The purpose of this study is to gauge the level of awareness about Cryptocurrency among investors and also investors attitude towards investing in Cryptocurrency. Impact of Coronavirus and the resultant lockdowns have made people realize the importance of having multiple sources of income. At the same time, Cryptocurrency has gained popularity in the Indian markets to greater heights. This study will help to understand whether this popularity can be converted into actual investment in cryptocurrency. This study aims to study mindset of investors belonging to different age, different financial backgrounds towards investment in cryptocurrency.